The Social Neuroscience of Empathy - Decety, Jean; Ickes, William (MIT Press, 2009)
Cross-disciplinary, cutting-edge work on human empathy from the perspectives of social, cognitive, developmental and clinical psychology and cognitive/affective neuroscience.In recent decades, empathy research has blossomed into a vibrant and multidisciplinary field of study.